China's enhanced urban wastewater treatment increases greenhouse gas emissions and regional inequality. (15th February 2023) - Huang, Yujun; Meng, Fanlin; Liu, Shuming; Sun, Siao; Smith, Kate
Highlights: Sludge and electricity affect the most in GHG emissions growth. Higher influent concentration leads to higher operation efficiency in bigger cities. The regional inequality in GHG emissions becomes increasingly significant. GHG control strategy in wastewater treatment should suit local conditions. Abstract: Sustainable water pollution control requires understanding of historical trajectories and spatial characteristics of greenhouse gas (GHG) emissions from wastewater treatment plants (WWTPs), which remains inadequately studied. Here, we establish plant-level monthly operational emissions inventories of China's WWTPs in 2009–2019. We show that urban wastewater treatment has been enhanced with 80% more chemical oxygen demand being removed annually. However, this progress is associated with 180% more GHG emissions at the national level, up to 58.3 Mt CO2 eq in 2019. We found significant seasonality in GHG emissions. Increasing sludge yield and electricity intensity became primary drivers after 2015 because of stricter standards, causing GHG emissions increase 12.9 and 8.3% until 2019. GHG emissions from urban wastewater treatment show high spatial difference at province, city and plant levels, with different sludge disposal and energy mix approaches combined with different influent and effluent conditions in WWTPs across China. Stricter effluent standard resulted in similar GHG emissions growth pattern in cities. We argue WWTPs focus on resource recovery in developed areas and higher operational efficiency in developing areas. Graphical abstract: Image, graphical abstract